Application of Biological Agents for The Control of Ganoderma sp. On Sengon Stands On North Kalimantan Post-Mining Land - Herliyana, Elis Nina; Azahra, Kharisma Aulia; Mansur, Irdika (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2025)
The land reclamation at PT. Pesona Khatulistiwa Nusantara using sengon trees is susceptible to pest and disease attacks, particularly red root rot disease caused by Ganoderma sp. This research aims to analyze the influence of biological agents, namely, the Trichoderma sp. and the JakabaBHP01 in inhibiting the growth of the Ganoderma sp. and analyze the influence of time in the inhibition process. The antagonist test was carried out using a double culture method between pathogenic fungi and antagonist fungi on Potato Dextrose Agar (PDA) media. The influence of time was treated in two ways: a) growing Ganoderma sp. and antagonistic fungi simultaneously and b) growing Ganoderma sp. for 7 days before testing its inhibitory power against antagonistic fungi. Antagonist test results showed that Trichoderma sp. and JakabaBHP01 can inhibit the growth of pathogens with simultaneous laying times. The highest inhibition results on Ganoderma sp. A1 was a treatment using Trichoderma sp., which is 95.63%, and in Ganoderma sp. A2 also had the highest inhibition with Trichoderma sp., 98.74%. Inhibitory mechanisms in Trichoderma sp. were a competition mechanism and in JakabaBHP01 it was a mycoparasitism mechanism.